PEMBUATAN PUPUK ORGANIK DARI KOTORAN SAPI DAN JERAMI PADI DENGAN PROSES FERMENTASI MENGGUNAKAN BIOAKTIVATOR M-DEC - Ahmad Shobib (Fakultas Teknik Universitas Wahid Hasyim, 2020)
Cow manure can be used for making organic fertilizer because it contains nutrients such as Nitrogen (N), Phosphorus (P), and Potassium (K). Rice straw has a high C-Organic content. Adding straw compost will increase soil organic matter content. The study aims to determine the fermentation process that occurs so as to produce organic fertilize, know the effect of fermentation time and the effect of the composition of raw materials for cow manure and rice straw on the process of making organic fertilizer to the content of organic fertilizer according to SNI 7603 : 2018. The method use by aerobic fermentation is by mixing cow manure and rice straw and M-Dec bioactivators by comparison 3 : 1, 2 : 2,1 : 3 and fermentation time 7, 14, 21, 28 days. The parameters tested are C-organic, Nitrogen (N), C/N ratio, Phosphorus (P), and Potassium (K). The best quality organic fertilizer in the treatment of cow manure : rice straw with a ratio of 2 : 2 on the 28th day fermentation process namely C-organic content 34,63 %, C/N ratio is 25, macro nutrient content N+P2O5+K2O of 3,14 % that has met SNI 7763 : 2018. Keyword: M-Dec bioactivator, aerobic fermentation, cow manure, rice straw, C/N ratio